Поліморфізм генів помірної нерасоспецифічної стійкості до хвороб Sr2/Lr27 та Lr34/Yr18/Pm38 у сортах м'якої пшениці ННЦ «Інститут землеробства НААН» - Заїка, Є.В.; Созінов, О.О.; Карелов, А.В.; Козуб, Н.О.; Філенко, О.Л.; Созінов, І.О. (Фактори експериментальної еволюції організмів, 2013)
Aims. The object of our investigation is allelic state identification of Sr2/Lr27 and Lr34/Yr18/Pm38 gene in bread wheat cultivars of Polissia. Methods. Allelic state of the Lr34 gene was identified with the molecular-genetic marker caISBP1 use and marker for Sr2/Lr27 locus was csSr2. Results. In five cultivars (13,5 % of the total number) was detected the «Marquiz-allele» and rest had the «null allele» of Sr2 locus. The «resistant» allelic state of Lr34 gene (Lr34+) was identified in 11 cultivars (39 %). The «susceptible» allelic state of Lr34 was identified in 9 wheat cultivars (32 %) and 8 (29 %) cultivars showed polymorphism at the Lr34 locus. Conclusions. It is necessary to involve in wheat breeding process the Lr34 and Sr2 gene, because it is valuable source of disease resistance.